Pelatihan Pembuatan Sabun Organik Kepada Ibu-Ibu PKK Desa Kemumu Kabupaten Bengkulu Utara (Universitas Bengkulu, 2024)
Lemongrass is a spice plant and was used by our ancestors as a cooking spice and to add a fragrant aroma to dishes. The content of secondary metabolite compounds in lemongrass can function as an antimicrobial and provide a refreshing fragrant aroma, so it can be used in organic soap. Apart from functioning as a cleanser, soap must also have added value, such as soap with added plant extracts, which has nutritional and nutritional value which is very necessary for the skin. Lemongrass extract added to soap making can help maintain skin by retaining skin moisture, helping the growth of new cells and preventing skin infections. This activity aims to increase the knowledge of PKK women in Kemumu Village, North Bengkulu Regency in making soap that is healthier and has added value. This program is a forum for socializing how to make healthy and natural products. Keywords : Kemumu, Organic Soap, Lemongrass Extract